Bacteriological and molecular study of Pseudomonas aeruginosa strains isolated from different clinical cases in Erbil and Kurkuk: Asif Hasan Abdul Razzaq1; Abdul Wahab Bedawi Al-Kubaisi1; Leqaa Majeed Aziz1 and Ali Saleh Hussain2 - Abdul Razzaq, Asif Hasan (The Iraqi Journal of Veterinary Medicine, 2018)
This study included isolates of bacteria from 125 clinical samples in Erbil and Kirkuk Hospital including (burns, wounds, urine and sputum); 38 isolates were identified as P. aeruginosa after conducting microscopic and biochemical tests. The results of antibiotic sensitivity test showed that all isolates of P. aeruginosa were different in resistance to Pipracillin, Erythromycin with rate of (100%) and to the Nalidixic acid (94.73%) while the lowest resistant antibiotics were to Co-trimoxazole, Ceftazidime and Ciprofloxacin, which amounted to (26.31%, 23.68 and 21.05%) respectively. For molecular diagnosis of P. aeruginosa some virulence genes the alg D and exo A were amplified through Polymerase Chain Reaction technique. The results showed that in 38 isolates cases only 22 (57.9%) were positive for algD gene by amplification of 520 bp band. While in urinary tract infection; 6 samples (60%) had alg D gene, and 8 (57.14%) isolates had alg D gene in wounds samples; also 7(70%) isolates from burns had that gene, while the sputum samples showed only one with alg D gene which was the lowest ratio; but in amplification of exo A, the results showed the presence of only one isolate from burns with molecular weight 396 bp with no appearance in others.